Mauritius : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper and Statistical Appendix analyzes the labor market of Mauritius. It highlights that the high level of youth unemployment in Mauritius points to deficiencies in education and training. There are also significant rigidities in the functioning of the labor market that aggravate the problem. In particular, the Mauritian labor market is highly regulated and the relevant institutions operate according to a legalistic approach in which economic criteria play a relatively minor role.